Small Bowel Obstruction Secondary to Obturator Hernia: A Pre-Operative Diagnosis at Computed Tomography / Marlina Tanty Ramli Hamid ...[et al.] - Ramli Hamid, Marlina Tanty; Mohd Khalid, Mohd Shukry; Rahmat, Kartini (Universiti Teknologi MARA Cawangan Selangor, 2021)
Obturator hernia is rare, but it must be considered in elderly patients who present with small bowel obstruction. The diagnosis is challenging unless there is a high index of suspicion as the presenting symptoms and signs are usually non-specific. Presence of positive Howship- Romberg sign is considered pathognomonic. Early diagnosis and rapid surgical intervention will reduce the high morbidity and mortality associated with undiagnosed obturator hernia. We report a case of a 93-year-old female patient who was admitted to our surgical department with symptoms of intestinal obstruction of 3-days duration. Howship-Romberg sign was negative. Computed tomography (CT) demonstrated the presence of left obturator hernia with proximal small bowel obstruction and no sign of strangulation. The patient had emergency laparotomy post-CT where the incarcerated bowel loop was released and the obstructed bowel was decompressed without any complication. The hernial defect was close with a mesh and the patient had an uneventful recovery post-surgery. In this case, we highlight that diagnosis of obturator hernia must always be considered in elderly patients who present with intestinal obstruction. Urgent CT could establish a rapid pre-operative diagnosis and aids in appropriate surgical intervention planning which is crucial in optimising the outcome.